Da'wah Communication in Sunda Wiwitan Community - Enjang As (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
Da'wah in the Baduy Indigenous people who have firmness in carrying out the Slamsundawiwitan religion or religion has a number of uniqueness, because even though the process of preaching is only limited to the conventional da'wah movement but has shown significant success. Besides there have been many Baduy Dangka people who embrace Islam, there have also been many absorption terms taken from words or terms from Islam used by the Baduy community in social interaction activities in the midst of their daily lives. The focus of this research is how the da'wah communication in the Outer Baduy Indigenous Peoples who adheres to the Slamsundawiwitan religion or religion. The purpose of his research is to analyze and describe the Slamsundawiwitan religion adopted by the Baduy Indigenous people, and preaching communication in the hands of the Baduy Indigenous people who embrace Slamsundawiwitan religion in Ciboleger village, Bojongmenteng Village, Leuwidamar District, Lebak Regency, Banten. This research is based on Herbert Blummer's Symbolic Interactionism Theory which is then derived in three dimensions, namely: Mind, Self and Society. While the research procedure uses the type of qualitative research with the case study method, so the data collection techniques use in-depth interviews and participatory observation. Because of that the data analysis technique is culaitative which only does general categorization and conclusions, and does not generalize. Dakwah pada masyarakat Adat Baduy yang memiliki keteguhan dalam menjalankan kepercayaan atau agama Slamsundawiwitan memiliki sejumlah keunikannya, karena sekalipun proses dakwahnya hanya sebatas gerakan dakwah konvensional tetapi telah menunjukkan keberhasilan yang cukup signifikan. Selain telah terdapat banyak masyarakat Baduy Dangka yang memeluk Islam juga telah banyak istilah serapan yang diambil dari kata atau istilah dari Islam digunakan oleh masyarakat Baduy dalam kegiatan interaksi sosial di tengah kehidupannya sehari-hari. Fokus penelitian ini adalah bagaimana komunikasi dakwah pada Masyarakat Adat Baduy Luar yang menganut kepercayaan atau agama Slamsundawiwitan. Tujuan penelitiannya untuk menganalisis dan mendeskripsikan tentang agama Slamsundawiwitan yang dianut masyarakat Adat Baduy, dan komunikasi dakwah di tangah masyarakat Adat Baduy yang menganut agama Slamsundawiwitan di kampung Ciboleger Desa Bojongmenteng Kecamatan Leuwidamar Kabupaten Lebak  Banten. Penelitian ini didasarkan pada Teori Interaksionisme Simbolik Herbert Blummer yang kemudian diturunkan dalam tiga dimensi, yaitu: Mind, Self dan Society. Sedangkan prosedur penelitianya menggunakan jenis penelitian kualitatif dengan metode studi kasus, sehingga teknik pengumpulan datanya menggunakan wawancara mendalam dan observasi partisipatif. Karena itu teknik analisis datanya bersifat kulaitatif yang hanya melakukan kategorisasi dan kesimpulan umum, serta tidak melakukan generalisasi.